Short Communication: Seed germination, seedling survival and storage behavior of Koompassia excelsa (Leguminosae) - Dian Latifah; Fitri Fatma Wardani; Rizmoon Nurul Zulkarnaen (Smujo International, 2020)
Abstract. Latifah D, Wardani FF, Zulkarnaen RN. 2020. Seed germination, seedling survival and storage behavior of Koompassia excelsa (Leguminosae). Nusantara Bioscience 12: 46-49. Koompassia excelsa (Becc.) Taub. (Leguminosae) is an important component of many tropical rainforests as an emergent canopy tree. Knowledge and application of germination strategies and increasing seedling survival of this species in many conservation efforts are essential as it is endemic to several areas in Southeast Asia. This research investigated the effects of the different moisture levels of the sowing media on the germination and seedling survival percentage of K. excelsa. The seeds exhibited faster germination percentage and higher seedling survival when sown in media with 33.2%-moisture. The seeds appeared to have intermediate storage behavior. Thus, sowing seeds in 33.2%-moisture media may promote seedling survival, which is an important part of regeneration as well as conservation of K. excelsa.